Serum CA 19-9 and CA 125 as a diagnostic marker in carcinoma of gallbladder - Manoj K Bind; Ravi R Mishra; Varsha Kumar; Vatsala Misra; Premala A Singh (Wolters Kluwer Medknow Publications, 2021)
Background: Gall bladder carcinoma is endemic in North India along the Ganges belt. Most of the cases usually present in late stage when prognosis is poor. That mandates a necessity for proper screening in these areas for gall bladder lesions. Tumor markers CA 19-9 and CA 125 have been studied in various GI cancers and may also help in the screening, diagnosis and evaluation of gall bladder carcinoma. Aims: To assess serum CA19-9 and serum CA125 in patients with gall bladder lesions and find out a cut off value for diagnosis of carcinoma gallbladder. Methods and Material: Study included 118 cases, with female: male ratio of 4:1.Out of it, 91 (77 %) cases were benign and 27 (23 %) were malignant. Patients' sera was collected and analyzed for CA19-9 and CA 125 by CMIA method. Results: The Mean (SD) value of CA19-9 for benign and malignant cases was found to be 12.86 (17.54) and 625.35(186.52) U/ml. For CA 125 it was found to be 17.98(13.69) and 239.63(73.72) U/ml respectively. The difference was statistically significant (P< 0.001). When Mean - 2SD value of malignant lesions were taken as cut off a value of CA 19-9 and CA 125 were found be 252.31 U/ml & 92.19U/ml respectively, found to be significant to suggest /diagnose a case of carcinoma gall bladder along with clinicoradiological findings. Taking these value as cut off Sensitivity & Specificity for CA 19-9 and CA 125 in detecting malignant cases were found to be 100% & 98.90% and 100% & 94.50% respectively. Conclusions: It is concluded that both serum CA 19-9 and serum CA 125 may act as a good adjunct for diagnosis of cases of carcinoma gallbladder along with imaging studies. However, changes in CA19-9 are more significant than CA 125.